High-Resolution Enabled 5-plex Mass Defect-based N,N-Dimethyl Leucine Tags for Quantitative Proteomics - Zhong, Xiaofang (Anal Chem, 2019)
Mass defect-based labeling strategy provides high accuracy as an MS(1)-centric quantification method, avoiding the ratio compression that affects isobaric label-based reporter ion quantification. We have developed cost-effective 5-plex mass defect N,N-dimethyl leucine (mdDiLeu) tags for quantification of various biological samples with increased multiplexing at a given resolving power afforded by the addition of mass difference isotopologues. The combination of mass difference and mass defect produces two labeled peak clusters separated by 5 Da in MS(1) spectra that are detected as five isotopic peaks at high resolution with mass difference of 15, 17, and 18 mDa per tag. Synthesis of each of the 5-plex mdDiLeu tags is accomplished by a single straightforward reaction step, making it accessible to any lab. To demonstrate 5-plex mdDiLeu for quantitative proteomics, we perform proof-of-principle experiments of mdDiLeu-labeled Saccharomyces cerevisiae lysate digest on an Orbitrap Fusion Lumos mass spectrometer.